Video-assisted thoracoscopic surgery for preventing and managing post-traumatic empyema: a narrative review - Misheva, Bojana; Chaulk, Richard C.; Nayak, Rahul (Video-Assisted Thoracic Surgery, 2026)
Background and Objective: Post-traumatic empyema is a serious complication of thoracic trauma, often arising from inadequately drained retained hemothorax. While most thoracic trauma can be managed non-operatively, the optimal strategy for preventing and managing empyema remains debated. Video-assisted thoracoscopic surgery (VATS) has emerged as a minimally invasive and effective technique for managing retained hemothorax and post-traumatic empyema. This narrative review aims to summarize current evidence and clinical guidelines regarding the use of VATS in preventing and managing post-traumatic empyema.Methods: A literature search of PubMed/MEDLINE, Google Scholar, and Western University Libraries Database was conducted from April 1, 2025, to June 1, 2025, limited to English-language publications. The review focuses on the pathophysiology, risk factors, diagnostic strategies, and management options for post-traumatic empyema, with particular emphasis on the role, timing, and comparative effectiveness of VATS.Key Content and Findings: Retained hemothorax occurs in up to 30% of thoracic trauma patients and may progress to empyema in approximately one-third of cases if inadequately treated. Early intervention, ideally within 3–7 days of injury, is critical to prevent the development of organized empyema. VATS has demonstrated superiority over thoracotomy and intrapleural fibrinolytics in select patients, offering reduced morbidity, faster recovery, and lower complication rates. Guidelines recommend early VATS for retained hemothorax unresponsive to chest tube drainage, as it minimizes progression to empyema and reduces the need for open surgery.Conclusions: VATS is a safe, effective, and minimally invasive approach for preventing and managing post-traumatic empyema in stable patients with retained hemothorax. Early use of VATS improves patient outcomes, reduces complications, and limits the need for more invasive procedures. Future research should aim to refine patient selection criteria and expand the indications for VATS in trauma care.